2002
DOI: 10.1029/2001gb001823
|View full text |Cite
|
Sign up to set email alerts
|

A multiisotope C and N modeling analysis of soil organic matter turnover and transport as a function of soil depth in a California annual grassland soil chronosequence

Abstract: [1] We examine soil organic matter (SOM) turnover and transport using C and N isotopes in soil profiles sampled circa 1949, 1978, and 1998 (a period spanning pulse thermonuclear 14 C enrichment of the atmosphere) along a 3-million-year annual grassland soil chronosequence. Temporal differences in soil D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
191
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(209 citation statements)
references
References 69 publications
17
191
0
1
Order By: Relevance
“…Values of δ 15 N increased with depth, as has been observed before (e.g. Mariotti et al, 1980;Baisden et al, 2002b), and were on average 1.7‰ (s.d. ±0.8‰) larger in the mOM fraction.…”
Section: Resultssupporting
confidence: 59%
“…Values of δ 15 N increased with depth, as has been observed before (e.g. Mariotti et al, 1980;Baisden et al, 2002b), and were on average 1.7‰ (s.d. ±0.8‰) larger in the mOM fraction.…”
Section: Resultssupporting
confidence: 59%
“…These results argue that the traditional ecological perspective of POC as fragmented and egested leaf litter (Vannote et al 1980) requires modification to include mineral-core and algal-derived particles as components of the suspended load. Furthermore, our results detail variability in POC fluxes and quality (i.e., carbon content of seston), which control carbon bioavailability (Baisden et al 2002) and should ultimately influence rates of heterotrophic respiration in downstream rivers (Mayorga et al 2005). Future work is needed to advance the understanding of the role of river networks in controlling the transformations of allochthonous and autochthonous POC transported from inland waters to the oceans.…”
Section: Discussionmentioning
confidence: 99%
“…Oelbermann and Voroney (2011) evaluated the ability of the CENTURY model (Parton et al, 1987) to predict SOC stocks in tropical and temperate agroforestry systems, but with a singlelayer modeling approach (0-20 cm). The approach of modeling a single topsoil layer assumes that deep SOC does not play an active role in carbon cycling, while it was shown that deep soil layers contain important amounts of SOC (Jobbagy and Jackson, 2000) and that part of this deep SOC could cycle on decadal timescales due to root inputs or dissolved organic carbon transport (Baisden and Parfitt, 2007;Koarashi et al, 2012). The need to take into account deep soil layers when modeling SOC dynamics is now well recognized in the scientific community (Baisden et al, 2002;Elzein and Balesdent, 1995), and several models have been proposed (Braakhekke et al, 2011;Guenet et al, 2013;Koven et al, 2013;Taghizadeh-Toosi et al, 2014;Ahrens et al, 2015).…”
mentioning
confidence: 99%